2002
DOI: 10.1021/jp020479c
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Catalyst and Support. 4. Periodic Trends and Patterns in Interactions of First-Row Transition Metals with the Silica Surface

Abstract: A “double-hump” pattern and a systematic trend of adsorption energies of the first-row transition metal atoms (Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), adsorbed on the surface of silicon dioxide, has been revealed by all-electron density functional theory (DFT) calculations. The study employs periodic DFT at the full-potential linearized augmented plane wave (FP-LAPW) level with spin-polarization taken into account. The geometry of the adsorbed atoms and the silica surface is optimized. The double-hump depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Namely, adsorption on silica tends to be stronger than on magnesia but weaker than on graphene, as revealed by E adh values (per contact atom) of À1.1, 72 À0.23, 75 and À2.07 eV 73 for Au 5 clusters on silica, magnesia, and graphene, respectively. On the other hand, calculation of E adh for one metal atom on silica 76 shows Ni (E adh = À1.90 eV) to adsorb more strongly than Fe (E adh = À1.70 eV), but more weakly than Co (E adh = À2.20 eV). However, on magnesia, 77 Ni adsorbs more strongly (E adh = À1.32 eV) than both Fe (E adh = À0.91 eV) and Co (E adh = À0.81 eV).…”
Section: Methodsmentioning
confidence: 99%
“…Namely, adsorption on silica tends to be stronger than on magnesia but weaker than on graphene, as revealed by E adh values (per contact atom) of À1.1, 72 À0.23, 75 and À2.07 eV 73 for Au 5 clusters on silica, magnesia, and graphene, respectively. On the other hand, calculation of E adh for one metal atom on silica 76 shows Ni (E adh = À1.90 eV) to adsorb more strongly than Fe (E adh = À1.70 eV), but more weakly than Co (E adh = À2.20 eV). However, on magnesia, 77 Ni adsorbs more strongly (E adh = À1.32 eV) than both Fe (E adh = À0.91 eV) and Co (E adh = À0.81 eV).…”
Section: Methodsmentioning
confidence: 99%
“…The periodic models of silica are based on the β-cristobalite structure . Although the high surface area silica is a noncrystalline material, it was reported that its local structure resembles specific faces of β-cristobalite whose bulk density and refractive index are close to those of amorphous silica. , In the previous works , and in a number of other computational studies, the β-cristobalite structure was used to model amorphous silica.…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…The high surface area silica is an amorphous material, and modeling its surface is a difficult task. On the basis of 29 Si NMR, 1 H NMR, and IR results, both geminal and single as well as hydrogen-bonded and isolated silanols are distinguished on the silica surface. It was reported that the structure of amorphous silica resembles that of β-cristobalite, and the kinds and concentration of the surface hydroxyl groups on silica and on β-cristobalite are also similar. ,,, Therefore, many theoretical simulations of amorphous silica are based on the β-cristobalite structure. On the fully hydroxylated (100) plane of β-cristobalite, all the silanols are of geminal type. Hydroxyl groups of adjacent geminal pairs can form hydrogen bonds, which facilitate partial dehydroxylation at elevated temperatures, leading to siloxane linkages and isolated hydroxyls, so-called vicinal silanols. ,,,, , On the other hand, only isolated single hydroxyl groups can be present on the (111) surface of β-cristobalite. ,,,,, It is proposed that real silica surface contains segments resembling both (100) and (111) faces of β-cristobalite. ,, …”
Section: Models Of Silica Surfacementioning
confidence: 99%